The influence of the managerial functions of the head of the room on the performance of nurses in performing nursing care in RS Royal Prima Medan 2020 - Wulandari, Beni; Ginting, Chrismis Novalinda; Lubis, Yoland Eliza Putri; Girsang, Ermi (International Journal of Research in Medical Sciences, 2021)
Background: Managerial function consisting of planning, organizing, actuating and the controlling. This study aimed to determine the effect of head of ward managerial function on the performance of individual nurses in implementing nursing care at inpatient room of public hospital Royal Prima Medan. Methods: The purpose of the study was to determine the effect of the managerial function of the head of room on the performance of nurses in carrying out nursing care in the Royal Prima Medan hospital. Type of research quantitative observational analytic design cross sectional study. Sample with purposive sampling of at least 15 respondents. Results: On the results obtained the influence between the planning function (p=0.919) there is no relationship between individual performance, organizing function (p=0.020) there is an influence of the relationship between individual performance, the function of direction (p=0.919) there is no relationship between individual performance and the supervisory function (p=0.020) there is an influence of the relationship between individual performance. Conclusions: The results of this study are used as input and material for consideration for the Royal Prima Medan hospital in making decisions, especially in addressing the problem of managerial function so that the Royal Prima Medan hospital is growing and can carry out managerial functions properly.